Manufacture of Hand Sanitizer and Liquid Soap in Pinang Dalam and Pinang Luar Villages - Eva Pramuni Oktaviani Sitanggang; Rinjani Ratih Rakasiwi; Wivina Diah Ivontianti; Lalak Tarbiyatun Nasyin Maleiva; Zainal Abidin (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic has hit the whole world, including Indonesia. Many attempts had been deftly conducted by the Government as a countermeasure so that this virus does not spread further and the cases can decrease. However, among all the implemented efforts, liquid soap and hand sanitizer have not been produced. Therefore, the socialization for the production of liquid soap and hand sanitizers were carried out to the residents of Pinang Luar Village and Pinang Dalam Village, Kubu Raya Regency, West Kalimantan, as residents of remote villages who had difficulty accessing the health protocol necessaries. Through this project, the residents expectedly can have the skills to produce them independently and avoid the dangers of COVID-19. Keywords: COVID-19, hand sanitizer, liquid soap